An efficient scalable batch-rekeying scheme for secure multicast communication using multiple logical key trees - Zakaria, Omar; Hassan Abdalla Hashim, Aisha; Hassan, Wan Haslina (IJCSNS, 2014)
Security is vital for many multicast-based application and services. Secure group key management is on of the challenging problems for multicast communication with large number of members. Where for each membership variation the group key must be updated and redistributed to all currently active members only. This causes a higher communication overhead in large size multicast group with high number of users joining or leaving the group. Logical Key Hierarchy which uses the key tree structure is proposed to reduce the communication cost of rekeying procedure and reduces the required number of rekeying messages. Furthermore, batch rekeying is proposed to reduce the rekeying cost by preform rekeying in predefined intervals instead of updating the keys after each join or leave. In this paper, a new scheme based on multiple key trees is proposed. Instead of using only a single key tree multiple key trees are used and at the end of each batch time the algorithm decides which tree will be used to update the keys. This paper shows that utilizing multiple key trees can efficiently decrease the rekeying communication overhead using batch rekeying scheme in tree-based architecture.